Government intervention on organic fertilizer promotion: a key to enhancing soil health and environment - Amgai, Sujan; Paudel, Santosh Raj; Bista, Diwas Raj; Poudel, Salik Ram (Journal of Agriculture and Environment, 2018)
Unilateral use of chemical fertilizers, devoid of organic sources, has led to gradual deterioration of soil health, exacerbating the agricultural productivity. This study focuses on the review the performance, effectiveness and modality of organic manure promotion programmes intervened by MoAD, using secondary datas. Major programmes intervened are: Vermi-compost production, cattle shed improvement, organic fertilizer industries establishment and price subsidy to farmers purchasing organic fertilizers. Study shows that these programs are effective to reduce soil health deterioration by making nutrient rich manure available at local level. Moreover, it has helped to reduce dependency of fertilizers on other countries and to promote sustainable agriculture. Altogether 1495 vermi-compost pits were constructed and 33746 cattle sheds were improved all over the country till FY 2072/73. Converting farm and household organic wastes into organic manure, improvement of the nutrient content of FYM, utilization of cattle urine for plant protection measures were the benefits of these programs. Furthermore, in long run it helps to create green economy by reducing pollution by keeping environment safe and clean.